Gene fusions and oncogenic mutations in MLH1 deficient and BRAFV600E wild-type colorectal cancers - Ukkola Iiris; Nummela Pirjo; Kero Mia; Tammio Hanna; Tuominen Jenni; Kairisto Veli; Kallajoki Markku; Haglund Caj; Peltomäki Päivi; Kytölä Soili; Ristimäki Ari (Springer, 2022)
Gene fusions can act as oncogenic drivers and offer targets for cancer therapy. Since fusions are rare in colorectal cancer (CRC), their universal screening seems impractical. Our aim was to investigate gene fusions in 62 CRC cases with deficient MLH1 (dMLH1) and BRAFV600E wild-type (wt) status from a consecutive real-life series of 2079 CRCs. First, gene fusions were analysed using a novel FusionPlex Lung v2 RNA-based next-generation sequencing (NGS) panel, and these results were compared to a novel Idylla GeneFusion assay and pan-TRK immunohistochemistry (IHC). NGS detected seven (7/62, 11%) NTRK1 fusions (TPM3::NTRK1, PLEKHA6::NTRK1 and LMNA::NTRK1, each in two cases, and IRF2BP2::NTRK1 in one case). In addition, two ALK, four RET and seven BRAF fusions were identified. Idylla detected seven NTRK1 expression imbalances, in line with the NGS results (overall agreement 100%). Furthermore, Idylla detected the two NGS-identified ALK rearrangements as one specific ALK fusion and one ALK expression imbalance, whilst only two of the four RET fusions were discovered. However, Idylla detected several expression imbalances of ALK (n = 7) and RET (n = 1) that were found to be fusion negative with the NGS. Pan-TRK IHC showed clearly detectable, fusion partner-dependent staining patterns in the seven NTRK1 fusion cases. Overall agreement for pan-TRK antibody clone EPR17341 was 98% and for A7H6R 100% when compared to the NGS. Of the 62 CRCs, 43 were MLH1 promoter hypermethylated (MLH1ph) and 39 were RASwt. All fusion cases were both MLH1ph and RASwt. Our results show that kinase fusions (20/30, 67%) and most importantly targetable NTRK1 fusions (7/30, 23%) are frequent in CRCs with dMLH1/BRAFV600Ewt/MLH1ph/RASwt. NGS was the most comprehensive method in finding the fusions, of which a subset can be screened by Idylla or IHC, provided that the result is confirmed by NGS.